2021
DOI: 10.3920/bm2020.0010
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between microbiota and metabolites after faecal microbiota transfer in irritable bowel syndrome

Abstract: Faecal microbiota transfer (FMT) consists of the infusion of donor faecal material into the intestine of a patient with the aim to restore a disturbed gut microbiota. In this study, it was investigated whether FMT has an effect on faecal microbial composition, its functional capacity, faecal metabolite profiles and their interactions in 16 irritable bowel syndrome (IBS) patients. Faecal samples from eight different time points before and until six months after allogenic FMT (faecal material from a healthy dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…For example, volatile fatty acids are abundant metabolites in faeces, and of these, butyric acid is well-known for its ability to enhance gut integrity and development, minimize inflammation and alleviate 'leaky gut' related issues [42][43][44]. As well as microbial metabolites in the donor inoculum itself, it has been reported that with IBS patients the microbemetabolite interactions seem to be disrupted after FMT [21]. Based on this, it is recommended that future equine FMT studies also include analysis of the metabolites in the donor inocula and the recipient's faeces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, volatile fatty acids are abundant metabolites in faeces, and of these, butyric acid is well-known for its ability to enhance gut integrity and development, minimize inflammation and alleviate 'leaky gut' related issues [42][43][44]. As well as microbial metabolites in the donor inoculum itself, it has been reported that with IBS patients the microbemetabolite interactions seem to be disrupted after FMT [21]. Based on this, it is recommended that future equine FMT studies also include analysis of the metabolites in the donor inocula and the recipient's faeces.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the limited efficacy of antimicrobial therapy which cannot alone restore the associated gut disturbances. FMT has also received interest in terms of ulcerative colitis [18], metabolic syndrome [19], irritable bowel syndrome [20,21] and, more recently, restoring the gut microbiota development of babies born by caesarean section [22]. FMT has also a long history in veterinary practice where it has value in the treatment of various gut-related disorders in cattle, although a strong evidence base behind this is limited in terms of scientific literature [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to metabolites, data extracted from the placebo group of clinical trials including IBS patients indicate that at least specific unique metabolites remain constant over time. 26,31,32 Another study, including only two IBS patients, demonstrated that the functional microbial profile measured at gene expression level was stable within subjects when having mild symptoms, but less stable when symptoms worsened. 47 While a recent study added important knowledge to the longitudinal aspects of both microbiota and metabolites in a larger cohort of IBS patients, they did not report the individual variation of the metabolite profiles over time.…”
Section: Discussionmentioning
confidence: 99%
“…(viii) Aroniadis and co-workers (2019) recruited people with diarrhea-predominant IBS and treated them with over 25 FMT capsules/day for three days (each capsule contained 0.38 g of minimally processed donor stool) but no improvement in symptoms was reported at three months in comparison with the placebo [ 120 ]. (ix) Holster and co-workers (2019) compared, in a small group of patients, FMT (via colonoscopy) using fecal material derived from a healthy donor (allogenic transplant) or from their own one (autologous transplant) finding no major differences in symptoms improvement between the two groups, despite an improvement in comparison to the baseline in the allogenic group [ 121 ]; the same research group found altered interactions between the gut microbiota and its metabolites [ 122 ] and an analysis of the RNA isolated from colonic biopsies before and after FMT revealed an activation of immune response-related genes in patients treated with allogenic FMT, and an activation of metabolism-related genes in those ones treated with autologous FMT [ 123 ].…”
Section: Fecal Microbiota Transplantation In Human Diseasesmentioning
confidence: 99%